Case Report: Hepatopulmonary fusion: to separate or not to separate? From a clinical case to A literature review - Tedesco, Marta; Costa, Simonetta; Agresti, Pierpaolo; Priolo, Francesca; Perri, Alessandro; Sbordone, Annamaria; Nobile, Stefano; Paradiso, Filomena Valentina; Stern, Maria Vittoria; Rizzo, Riccardo; Giustiniani, Maria Cristina; Nanni, Lorenzo; et al. (Frontiers in Pediatrics, 2025)
ObjectiveHepatopulmonary fusion (HPF) is a rare congenital malformation, frequently associated to right-sided congenital diaphragmatic hernia (CDHR). The presence of HPF often leads to a fatal outcome. The most effective approach to managing this condition remains uncertain due to the limited number of documented cases in the literature.Study designThis case presents a 11-day old full-term female neonate with HPF associated to CDHR. The definitive diagnosis of HPF was made during surgery for CDHR. Our team opted for a simple repair of the diaphragmatic defect and no attempts were made to separate the liver from the right lung.ResultsOur approach was successful, as our patient not only survived the procedure but also showed favorable cardiorespiratory adaptation, consistent growth, and regular neurodevelopment, according to follow-up data, available at six months of life.ConclusionThe adopted surgical management strongly suggests that when the diagnosis is made intraoperatively and detailed knowledge of the vascularization is lacking, partial separation of the viscera, preserving the medial hepatopulmonary fusion and suturing the diaphragm, is the successful approach.